Recurrence of chronic subdural hematoma due to low-grade infection - Dubinski, Daniel; Won, Sae-Yeon; Trnovec, Svorad; Gounko, Kseniya; Baumgarten, Peter; Warnke, Philipp; Cantré, Daniel; Behmanesh, Bedjan; Bernstock, Joshua D.; Freiman, Thomas M.; Gessler, Florian; Sola, Steffen (Frontiers in Neurology, 2022)
Despite the high incidence and multitudes of operative techniques, the risk factors for chronic subdural hematoma (CSDH) recurrence are still under debate and a universal consensus on the pathophysiology is lacking. We hypothesized that clinically inapparent, low-grade infection could be responsible for CSDH recurrence. This investigation is a single center prospective observational study including patients with recurrent CSDH. In total, 44 patients with CSDH recurrence received an intraoperative swab-based microbiological testing. The intraoperative swab revealed an inapparent low-grade hematoma infection in 29% of the recurrent CSDH cases. The majority (69%) of the identified germs belonged to the staphylococcus family. We therefore propose a novel potential pathophysiology for CSDH recurrence.